Oxidized bacterial cellulose-glycerol-tea polyphenol fresh-keeping coating material as well as preparation method and application thereof

Through the preparation of the oxidized bacterial cellulose-glycerol-tea polyphenol (OBC-GL-TP) fresh-preservation coating material, the problems of unstable fruit and vegetable fresh-preservation effects, single functions and pollution in the prior art are solved, and efficient, safe and long-lasting fruit and vegetable fresh-preservation effects are achieved.

CN119867142APending Publication Date: 2025-04-25SHANGHAI INST OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510094690.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-21
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The existing fruit and vegetable preservation technology has problems such as high equipment cost, large energy consumption, high technical complexity, residual contamination of chemical preservation agents, single function of bacterial cellulose, and poor stability of tea polyphenols, making it difficult to achieve efficient, safe and long-lasting fruit and vegetable preservation.

Method used

The bacterial cellulose is treated through oxidation technology and grafting reaction, which improves the load stability and sustained release effect of tea polyphenols, forms an oxidized bacterial cellulose-glycerol-tea polyphenol (OBC-GL-TP) fresh-preserving coating material, optimizes acid value, inhibits enzyme activity and reduces the total colony count, and comprehensively ensures the fresh quality of fruits and vegetables and extends the shelf life.

Benefits of technology

The stable load and sustained release of tea polyphenols are achieved, the antioxidant and antibacterial properties are improved, the oxidation and microbial erosion of fruits and vegetables are significantly delayed, the freshness and moisture of fruits and vegetables are maintained, and the shelf life is extended.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119867142A_ABST
    Figure CN119867142A_ABST
Patent Text Reader

Abstract

The invention relates to an oxidized bacterial cellulose-glycerol-tea polyphenol fresh-keeping coating material as well as a preparation method and application thereof. The method comprises the following steps: crushing bacterial cellulose to prepare homogenate, and treating the homogenate by using an oxidation technology to obtain the oxidized bacterial cellulose. Then, glycerol is added into the oxidized bacterial cellulose for a grafting reaction, an oxidized bacterial cellulose-glycerol system is promoted to achieve effective loading on the tea polyphenol by means of ultrasonic treatment, and finally the oxidized bacterial cellulose-glycerol-tea polyphenol fresh-keeping coating material is prepared. The fresh-keeping coating material has excellent oxidation resistance and wide antibacterial property. By applying the coating, the freshness of fruits and vegetables can be effectively maintained, the acid value can be practically controlled, the total number of bacterial colonies can be reduced, the activity of catalase and polyphenol oxidase can be inhibited, and browning and decay of fresh fruits and vegetables can be delayed, so that the shelf life of the fruits and vegetables can be prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of fruit and vegetable preservation, and in particular to an oxidized bacterial cellulose-glycerol-tea polyphenols preservation coating material and a preparation method and application thereof. Background Art

[0002] In the field of food preservation, high requirements for food safety and quality have made the research and development of green, efficient and safe preservation technologies urgent.

[0003] Existing methods for preserving fruits and vegetables each have their own drawbacks. In terms of traditional physical preservation, although low-temperature refrigeration can reduce the physiological metabolic rate of fruits and vegetables to a certain extent, its large-scale application is limited by its high equipment purchase and operation costs, high energy consumption, and strict requirements on storage environment conditions; although controlled atmosphere preservation delays the aging of fruits and vegetables by regulating gas composition, its technical complexity is high, the equipment maintenance cost is high, and it is easily disturbed by external factors, resulting in unstable preservation effects. Chemical preservation methods rely on chemical synthetic preservatives, such as sulfur dioxide, benzoic acid and its salts. These substances remain on the surface of fruits and vegetables, which not only threatens human health, but also causes environmental pollution. Long-term use will also cause the deterioration of the color, taste and other qualities of fruits and vegetables.

[0004] As a natural polymer material, bacterial cellulose has attracted attention in the field of food preservation due to its high crystallinity, high water holding capacity, good biocompatibility and mechanical strength. However, relying solely on bacterial cellulose for preservation is difficult to effectively resist the quality deterioration caused by oxidation and microbial erosion during fruit and vegetable storage, as it has a single function and relatively weak antioxidant and antibacterial properties, and cannot fully meet the complex and diverse preservation needs.

[0005] Tea polyphenols, as natural antioxidants and antibacterial agents extracted from tea leaves, have the advantages of high efficiency, non-toxicity and no residue, and have great application potential in the field of food preservation. However, in actual applications, they have poor stability and are easily affected by the environment and lose their activity. Moreover, when used alone, they have poor adhesion and sustained release on the surface of fruits and vegetables, making it difficult to maintain a long-term preservation effect.

[0006] Patent CN106633156A discloses a method for preparing a bacterial cellulose-tea polyphenol composite antibacterial film, which is characterized in that bacterial cellulose is used as a raw material, combined with tea polyphenols, and a bacterial cellulose-tea polyphenol composite antibacterial film is prepared through the steps of preparing bacterial cellulose hydrogel, purifying, preparing a composite film, and forming a film. The defects of bacterial cellulose, such as lack of antibacterial properties and brittleness and fragility, are solved by combining it with tea polyphenols to form a film, forming a bacterial cellulose-tea polyphenol composite antibacterial film preparation process, improving the antibacterial properties of the composite film, enhancing its functional properties, and providing better raw materials for the food packaging industry. Patent CN102212209B discloses a packaging film for refrigerated food and a preparation method thereof, which is characterized in that the packaging film is made of bacterial cellulose gel, and the bacterial cellulose gel contains the antibacterial component nisin. The steps of the packaging film preparation method for refrigerated food include: (1) purifying bacterial cellulose gel; (2) preparing an antibacterial solution; (3) adsorption and fixation of antibacterial components. This packaging film is not only non-toxic and harmless, but can also be eaten directly with food. It also has good air permeability and protective effects, especially has a good effect in inhibiting the growth of LM bacteria. It can also absorb a large amount of other antibacterial ingredients, which can effectively inhibit the reproduction of harmful bacteria and extend the shelf life of food.

[0007] However, the above patents have several shortcomings. Although patent CN106633156A combines bacterial cellulose with tea polyphenols to form an antibacterial film, there is a lack of in-depth research on how to further improve the stability of tea polyphenols in the composite film and the sustained antibacterial performance in complex environments. Its preparation process is relatively conventional, and it is insufficient in the fine regulation of the microstructure of the material, making it difficult to give full play to the maximum effectiveness of tea polyphenols, which may lead to a gradual decline in the preservation effect during long-term use. Patent CN102212209B focuses on the use of Nisin solution to inhibit the growth of LM bacteria and extend the shelf life of food, and there are limitations in the diversity of antibacterial ingredients. In addition, it does not provide effective solutions for optimizing the mechanical properties of packaging films, such as flexibility and tensile resistance, which may affect the convenience and durability in actual use.

[0008] Therefore, given the many defects of existing preservation technologies and materials, there is an urgent need for a food preservation solution to make up for the shortcomings of existing technologies and achieve efficient, safe and long-lasting fruit and vegetable preservation results. Contributing innovative solutions to the field of food preservation, meeting the market demand for high-quality preservation technology, and promoting the development of food preservation technology to a higher level. Summary of the invention

[0009] Based on the shortcomings of the above-mentioned prior art, the purpose of the present application is to provide an oxidized bacterial cellulose-glycerol-tea polyphenols fresh-keeping coating material and its preparation method and application.

[0010] The present invention treats bacterial cellulose through oxidation technology and grafting reaction, which greatly improves the loading stability and sustained release effect of tea polyphenols. At the microscopic level, the structure and physicochemical properties of bacterial cellulose are changed, so that a tighter and more stable combination is formed between bacterial cellulose and tea polyphenols, effectively avoiding the problem of rapid inactivation of tea polyphenols due to environmental factors. At the same time, the present invention is aimed at the specific needs of fruit and vegetable preservation, and systematic optimization is carried out in terms of controlling acid value, inhibiting enzyme activity and reducing total bacterial count, which can comprehensively guarantee the fresh quality of fruits and vegetables and extend the shelf life. Therefore, the present invention has higher innovation and application value in the field of food preservation coating materials, and is expected to fill the deficiencies of the prior art and promote the development of the industry.

[0011] The purpose of the present invention can be achieved by the following technical solutions:

[0012] One of the technical solutions of the present invention is to provide a method for preparing an oxidized bacterial cellulose-glycerol-tea polyphenol (OBC-GL-TP) fresh-keeping coating material, the preparation method comprising the following steps:

[0013] S1. Preparation / obtaining of bacterial cellulose (BC);

[0014] S2. crushing and oxidizing the bacterial cellulose to obtain oxidized bacterial cellulose (OBC);

[0015] S3. The oxidized bacterial cellulose (OBC) obtained in step S2 is mixed with glycerol and citric acid to carry out a grafting reaction to obtain oxidized bacterial cellulose-glycerol (OBC-GL);

[0016] S4. The oxidized bacterial cellulose-glycerol (OBC-GL) obtained in step S3 is mixed with tea polyphenols (TP) for reaction, so that the tea polyphenols (TP) are loaded on the oxidized bacterial cellulose-glycerol (OBC-GL), and the oxidized bacterial cellulose-glycerol-tea polyphenols (OBC-GL-TP) fresh-keeping coating material is obtained.

[0017] Furthermore, in step S1, the source of the bacterial cellulose is selected from any one of the bacteria of the genus Acetobacter, Agrobacterium, Rhizobium or Sarcina, and is obtained by fermentation of any of the above bacteria.

[0018] Furthermore, in some preferred embodiments of the present application, in step S1, the bacterial cellulose is prepared using Acetobacter xylinum as the strain; the Acetobacter xylinum is cultured statically or dynamically in a liquid culture medium at a constant temperature for 3-7 days, placed in a 1%-5% (w / v) sodium hydroxide solution, treated at 70-90°C for 2-4 hours, taken out, and rinsed with deionized water until neutral to obtain the bacterial cellulose.

[0019] Furthermore, in step S2, the bacterial cellulose is crushed to prepare a homogenate with a mass concentration of 0.1-2%, oxidized in a TEMPO / NaBr / NaClO mixed oxidation system at room temperature, and then centrifuged, washed and dialyzed to obtain oxidized bacterial cellulose.

[0020] TEMPO plays a role of selective oxidation in the system. It can selectively oxidize the primary hydroxyl groups on the bacterial cellulose chain to aldehyde groups, and then further oxidize to carboxyl groups, while having little effect on other functional groups and glycosidic bonds in the cellulose molecules. Therefore, it can achieve specific oxidative modification of bacterial cellulose under mild conditions, accurately introduce functional groups such as carboxyl groups, and change the properties of bacterial cellulose. By undergoing redox reaction cycles with other substances in the system, it promotes the oxidation reaction and plays a catalytic role, allowing the oxidation reaction to proceed more efficiently.

[0021] NaBr plays a role in promoting the reaction in the system. It can react with NaClO to generate active species such as Br2 or BrO- with stronger oxidizing properties. These active species can interact with TEMPO, accelerate the oxidation process of bacterial cellulose by TEMPO, and improve the reaction rate and oxidation efficiency. It can help regulate the redox potential of the system so that the reaction proceeds within a suitable potential range, which is conducive to TEMPO to exert its oxidizing effect, and can make the oxidation reaction more controllable and avoid the occurrence of side reactions such as over-oxidation.

[0022] NaClO is the main oxidant in the system, providing the oxidizing properties required for the oxidation reaction. It can release active oxygen in the system and oxidize TEMPO to its more active oxidation state, so that TEMPO can continue to oxidize bacterial cellulose. By continuously providing oxidizing properties, the system is maintained in an oxidizing environment, ensuring that the oxidation reaction can proceed smoothly, so that the oxidation reaction of bacterial cellulose can proceed in the expected direction, and the primary hydroxyl groups are gradually oxidized to aldehyde groups and carboxyl groups.

[0023] Further, in step S2, the oxidation time is 0.5-5h, preferably 0.5-3h, more preferably 0.5-2.5h, 1.5-2.5h.

[0024] In some preferred embodiments of the present application, the TEMPO / NaBr / NaClO mixed oxidation system is as follows: the TEMPO dosage is (0.1-1.0) g / 100 mL bacterial cellulose; the NaBr dosage is (0.1-1.0) g / 100 mL bacterial cellulose; the mass concentration of the NaClO solution is 8-12%, and the dosage is 8-10 mL.

[0025] The TEMPO dosage is preferably 0.1 g / 100 mL bacterial cellulose; the NaBr dosage is preferably 0.1 g / 100 mL bacterial cellulose; the mass concentration of NaClO is preferably 10%, and the dosage is 8 mL.

[0026] In some preferred embodiments of the present application, the mixed oxidation step is as follows: a bacterial cellulose homogenate with a mass concentration of 0.1-2% is mixed with TEMPO, NaBr, and NaClO, and then 0.1-0.2M (preferably 0.1M) sodium hydroxide is added to maintain the pH at 10±0.1. When the pH value no longer decreases, 10% ethanol is added to quench the reaction.

[0027] Further, in step S3, the ratio of oxidized bacterial cellulose, glycerol and citric acid is (1.0-10.0) g: (0.03-0.3) g: (0.02-0.2) g, the homogenization time is 10-30 min, and the mixing reaction is carried out at 80° C.-100° C. for 4-6 h.

[0028] Citric acid acts as a reaction catalyst in the grafting system, which reduces the activation energy of the reaction and allows the reaction to proceed smoothly without reaching a very high temperature.

[0029] Furthermore, in step S4, the mixing reaction time of the oxidized bacterial cellulose-glycerol (OBC-GL) and tea polyphenols (TP) is 30-60 minutes, and the mixing reaction is carried out under ultrasound.

[0030] The role of ultrasound is to strengthen the interaction between the active substance and the carrier. Its vibration can make the active substance contact more closely with the carrier surface, increase the physical adsorption force, van der Waals force, hydrogen bond, etc. between them.

[0031] The second technical solution of the present invention is to provide an oxidized bacterial cellulose-glycerol-tea polyphenol (OBC-GL-TP) fresh-keeping coating material, and the fresh-keeping coating is obtained based on the preparation method described in one of the technical solutions.

[0032] The third technical solution of the present invention is to provide an application of an oxidized bacterial cellulose-glycerol-tea polyphenol (OBC-GL-TP) fresh-keeping coating material, wherein the oxidized bacterial cellulose-tea polyphenol fresh-keeping coating is used for food preservation.

[0033] The beneficial effects of the present invention are:

[0034] (1) The raw material of the present invention, bacterial cellulose, is a natural dietary fiber obtained through a microbial fermentation process. It has the characteristics of being non-toxic, highly safe and renewable.

[0035] (2) The present invention adopts selectively oxidized bacterial cellulose, which is soluble in water and has a nanoscale three-dimensional network structure, so that it can provide a larger specific surface area and more interaction sites in the system; the oxidized bacterial cellulose is non-toxic and harmless to the human body and can be completely degraded in nature without causing pollution to the environment, which is in line with the current concept of environmental protection and sustainable development.

[0036] (3) The present invention constructs an oxidized bacterial cellulose grafted with glycerol system, which solves the problem that the oxidized bacterial cellulose has relatively large pores, low controlled release efficiency, and low efficiency in loading active substances. After grafting with glycerol, covalent bonds are generated to shrink the three-dimensional size as a whole, increase the amorphous area, and make the hydrogen bond network more complex and denser. The loading amount of tea polyphenols is increased to achieve precise controlled release.

[0037] (4) The fresh-keeping coating prepared by the present invention is a nanomaterial, which not only has excellent antioxidant and broad-spectrum antibacterial properties, but also can retain moisture for food (such as fresh walnuts), and can significantly maintain the freshness of food, including acid value, polyphenol oxidase and catalase activity, etc.

[0038] (5) The material of the present invention is in liquid form, which is convenient to use and can be precisely controlled. It has film-forming properties and is non-toxic and harmless to the human body without adding a film-forming agent. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1 The present invention is a process for preparing the active coating.

[0040] Figure 2 It is a graph showing the growth curve test results of oxidized bacterial cellulose-glycerol (OBC-GL), oxidized bacterial cellulose-tea polyphenols (OBC-TP), and oxidized bacterial cellulose-glycerol-tea polyphenols (OBC-GL-TP) on Escherichia coli and Staphylococcus aureus.

[0041] Figure 3 This is the test result graph of DPPH and ABTS free radical scavenging rate of OBC-GL, OBC-TP and OBC-GL-TP.

[0042] Figure 4 To investigate the changes of acid value during storage of fresh walnuts using OBC-GL, OBC-TP, OBC-GL-TP, and vacuum (without any treatment).

[0043] Figure 5 To study the changes in peroxidase values ​​during the storage of fresh walnuts using OBC-GL, OBC-TP, OBC-GL-TP, and vacuum (without any treatment).

[0044] Figure 6To study the changes in polyphenol oxidase activity during the storage of fresh walnuts using OBC-GL, OBC-TP, OBC-GL-TP, and vacuum (without any treatment). DETAILED DESCRIPTION

[0045] In order to enable those skilled in the art to better understand the technical solution of the present invention, the present invention is described in detail below in conjunction with specific embodiments. It should be noted that the following embodiments will help those skilled in the art to further understand the present invention, but do not limit the present invention in any form. It should be noted that for those of ordinary skill in the art, several variations and improvements can also be made without departing from the concept of the present invention. These all belong to the protection scope of the present invention.

[0046] All raw materials of the present invention have no particular limitation on their sources, and can be purchased from the market or prepared according to conventional methods known to those skilled in the art.

[0047] The deposit number of Acetobacter xylinum is ATCC 23770, American Type Culture Collection. Staphylococcus aureus (ATCC 6538) and Escherichia coli (ATCC 25922) were provided by China Industrial Culture Collection Center. Sodium hypochlorite was purchased from Shanghai Myrel Biochemical Technology Co., Ltd., glycerol was purchased from China National Pharmaceutical Chemical Reagent Co., Ltd. (Shanghai), and other reagents were purchased from Aladdin, dialysis bag MWCO: 3500-5000 0.79mL / cm pre-wet Repligen membrane series 3.5-5KD Riplegen. Electronic balance CP214 Ohaus Instrument Shanghai Co., Ltd., pH meter PHS-25C Shanghai Kangyi Instrument Co., Ltd., high-speed homogenizer XHF-DY Ningbo Xinzhi Biotechnology Co., Ltd., digital display heat collection magnetic stirrer DF-101S Beijing Zhongxing Weiye Century Instrument Co., Ltd. Ultrasonic cell crusher SM-650D Nanjing Shunma Instrument Equipment Co., Ltd., ultrasonic cleaner KQ2200 Kunshan Shumei.

[0048] Example 1

[0049] Preparation of Oxidized Bacterial Cellulose-Glycerol (OBC-GL) Graft System

[0050] (1) The bacterial cellulose membrane (BC membrane) used in the examples of the present application was prepared from the fixed fermentation culture of Acetobacter xylinum ATCC 23770. Acetobacter xylinum was used as the strain, and was cultured statically or dynamically at 30°C for 7 days in a liquid culture medium containing 3 g / L tryptophan, 25 g / L glucose and 5 g / L yeast extract (the pH value of the culture medium was adjusted to 5.0 with 80% (v / v) sulfuric acid) to obtain a bacterial cellulose membrane (BC membrane).

[0051] (2) The BC membrane was repeatedly washed with distilled water to remove residual culture medium components. After washing, the BC membrane was placed in a 1% (w / v) sodium hydroxide solution at 80°C for 4 hours to purify the BC membrane to remove residual bacteria and other organisms.

[0052] (3) The BC membrane was thoroughly washed with deionized water until the pH of the residual solution after washing was neutral. The washed BC membrane was autoclaved at 121°C for 20 minutes and stored at 4°C until further use.

[0053] (4) The bacterial cellulose membrane was crushed in an ultrasonic cell crusher with a power of 500 W and a crushing time of 4 minutes; then, the membrane was homogenized in a high-speed homogenizer at 10,000 rpm for 20 minutes to prepare a bacterial cellulose homogenate with a mass concentration of 0.1%.

[0054] (5) Take 200 mL of 0.1% bacterial cellulose homogenate, 0.2 g TEMPO, 0.2 g NaBr and 8 mL of 10% NaClO and mix them for oxidation reaction. During the reaction, 0.1 M sodium hydroxide is added to maintain the pH at 10 ± 0.1; the oxidation reaction lasts for 2.5 hours. When the pH value no longer decreases, 10% ethanol is added to quench the reaction. At this point, the reaction system contains oxidized bacterial cellulose (OBC), unreacted TEMPO, NaBr, residual NaClO, and possible by-products. In order to obtain a pure oxidized bacterial cellulose (OBC) solution, the mixed solution after the reaction needs to be dialyzed. Select a pretreated dialysis bag with a molecular weight cutoff of 100-500Da (MWCO: 100-500), place the dialysis bag containing the mixed solution into a glass container containing sufficient dialysis fluid, use deionized water as the dialysis fluid, and the volume of the dialysis fluid should be 50-100 times the sample volume to ensure the adequacy of dialysis. Place the glass container on a magnetic stirrer and set the stirring speed to 100-150rpm to keep the dialysis fluid in a uniform flow state and promote the diffusion of small molecule impurities. The entire dialysis process is carried out at a low temperature of 4°C. During the dialysis process, the dialysis fluid is tested regularly. In the early stage, the conductivity of the dialysate can be tested every hour with a portable conductivity meter to determine the leakage of small molecular ions; the dialysate should be replaced in time according to the test results. Within the first 3 hours of dialysis, the dialysate should be replaced every 1-2 hours; as the dialysis continues, the concentration of impurities in the dialysate gradually decreases, and the time interval for replacing the dialysate can be extended to once every 2-3 hours. When the conductivity of the dialysate remains basically unchanged for two consecutive tests, and no obvious impurity ions are detected by ion chromatography and other detection methods, it indicates that the dialysis has reached the end point. Take out the dialysis bag, gently absorb the moisture on the surface of the dialysis bag with filter paper, then open the dialysis bag, and transfer the solution in the bag to a clean container that has been sterilized at high temperature to obtain a relatively pure oxidized bacterial cellulose (OBC) solution.

[0055] (6) Oxidized bacterial cellulose, glycerol and citric acid were mixed in a ratio of 10.0 g: 0.3 g: 0.2 g, homogenized for 15 min, and reacted at 80° C.-100° C. for 4 h. Finally, oxidized bacterial cellulose-glycerol (OBC-GL) was obtained.

[0056] Example 2

[0057] Preparation of Oxidized Bacterial Cellulose-Tea Polyphenols (OBC-TP)

[0058] (1) The bacterial cellulose membrane (BC membrane) used in the examples of the present application was prepared from the fixed fermentation culture of Acetobacter xylinum ATCC 23770. Acetobacter xylinum was used as the strain, and was cultured statically or dynamically at 30°C for 7 days in a liquid culture medium containing 3 g / L tryptophan, 25 g / L glucose and 5 g / L yeast extract (the pH value of the culture medium was adjusted to 5.0 with 80% (v / v) sulfuric acid) to obtain a bacterial cellulose membrane (BC membrane).

[0059] (2) The BC membrane was repeatedly washed with distilled water to remove residual culture medium components. After washing, the BC membrane was placed in a 1% (w / v) sodium hydroxide solution at 80°C for 4 hours to purify the BC membrane to remove residual bacteria and other organisms.

[0060] (3) The BC membrane was thoroughly washed with deionized water until the pH of the residual solution after washing was neutral. The washed BC membrane was autoclaved at 121°C for 20 minutes and stored at 4°C until further use.

[0061] (4) The bacterial cellulose membrane was crushed in an ultrasonic cell crusher with a power of 500 W and a crushing time of 4 min; then, the membrane was homogenized in a high-speed homogenizer at 10,000 rpm for 20 min to prepare a bacterial cellulose homogenate with a mass concentration of 0.1%.

[0062] (5) Take 200 mL of 0.1% bacterial cellulose homogenate, 0.2 g TEMPO, 0.2 g NaBr and 8 mL of 10% NaClO and mix them for oxidation reaction. During the reaction, add 0.1 M sodium hydroxide to maintain the pH at 10 ± 0.1; the oxidation reaction lasts for 2.5 hours. When the pH value no longer decreases, add 10% ethanol to quench the reaction. At this point, the reaction system contains oxidized bacterial cellulose (OBC), unreacted TEMPO, NaBr, residual NaClO, and possible by-products. In order to obtain a pure oxidized bacterial cellulose (OBC) solution, the mixed solution after the reaction needs to be dialyzed. Select a pretreated dialysis bag with a molecular weight cutoff of 100-500Da (MWCO: 100-500), place the dialysis bag containing the mixed solution into a glass container containing sufficient dialysis fluid, use deionized water as the dialysis fluid, and the volume of the dialysis fluid should be 50-100 times the volume of the sample to ensure the adequacy of dialysis. Place the glass container on a magnetic stirrer and set the stirring speed to 100-150rpm to keep the dialysis fluid in a uniform flow state and promote the diffusion of small molecule impurities. The entire dialysis process is carried out at a low temperature of 4°C. During the dialysis process, the dialysis fluid is tested regularly. In the early stage, the conductivity of the dialysate can be tested every hour with a portable conductivity meter to determine the leakage of small molecular ions; the dialysate should be replaced in time according to the test results. Within the first 3 hours of dialysis, the dialysate should be replaced every 1-2 hours; as the dialysis continues, the concentration of impurities in the dialysate gradually decreases, and the time interval for replacing the dialysate can be extended to once every 2-3 hours. When the conductivity of the dialysate remains basically unchanged for two consecutive tests, and no obvious impurity ions are detected by ion chromatography and other detection methods, it indicates that the dialysis has reached the end point. Take out the dialysis bag, gently absorb the moisture on the surface of the dialysis bag with filter paper, then open the dialysis bag, and transfer the solution in the bag to a clean container that has been sterilized at high temperature to obtain a relatively pure oxidized bacterial cellulose (OBC) solution.

[0063] (6) Tea polyphenols (TP) were added to the oxidized bacterial cellulose solution at a concentration of 0.1 g / mL and subjected to ultrasonic loading for 15 min. Finally, oxidized bacterial cellulose-tea polyphenols (OBC-TP) was obtained.

[0064] Example 3

[0065] Preparation of Oxidized Bacterial Cellulose-Glycerol-Tea Polyphenols (OBC-GL-TP)

[0066] (1) The bacterial cellulose membrane (BC membrane) used in the examples of the present application was prepared from the fixed fermentation culture of Acetobacter xylinum ATCC 23770. Acetobacter xylinum was used as the strain, and was cultured statically or dynamically at 30°C for 7 days in a liquid culture medium containing 3 g / L tryptophan, 25 g / L glucose and 5 g / L yeast extract (the pH value of the culture medium was adjusted to 5.0 with 80% (v / v) sulfuric acid) to obtain a bacterial cellulose membrane (BC membrane).

[0067] (2) The BC membrane was repeatedly washed with distilled water to remove residual culture medium components. After washing, the BC membrane was placed in a 1% (w / v) sodium hydroxide solution at 80°C for 4 hours to purify the BC membrane to remove residual bacteria and other organisms.

[0068] (3) The BC membrane was thoroughly washed with deionized water until the pH of the residual solution after washing was neutral. The washed BC membrane was autoclaved at 121°C for 20 minutes and stored at 4°C until further use.

[0069] (4) The bacterial cellulose membrane was crushed in an ultrasonic cell crusher with a power of 500 W and a crushing time of 4 min; then, the membrane was homogenized in a high-speed homogenizer at 10,000 rpm for 20 min to prepare a bacterial cellulose homogenate with a mass concentration of 0.1%.

[0070] (5) Take 200 mL of 0.1% bacterial cellulose homogenate, 0.2 g TEMPO, 0.2 g NaBr and 8 mL of 10% NaClO and mix them for oxidation reaction. During the reaction, add 0.1 M sodium hydroxide to maintain the pH at 10 ± 0.1; the oxidation reaction lasts for 2.5 hours. When the pH value no longer decreases, add 10% ethanol to quench the reaction. At this point, the reaction system contains oxidized bacterial cellulose (OBC), unreacted TEMPO, NaBr, residual NaClO, and possible by-products. In order to obtain a pure oxidized bacterial cellulose (OBC) solution, the mixed solution after the reaction needs to be dialyzed. Select a pretreated dialysis bag with a molecular weight cutoff of 100-500Da (MWCO: 100-500), place the dialysis bag containing the mixed solution into a glass container containing sufficient dialysis fluid, use deionized water as the dialysis fluid, and the volume of the dialysis fluid should be 50-100 times the volume of the sample to ensure the adequacy of dialysis. Place the glass container on a magnetic stirrer and set the stirring speed to 100-150rpm to keep the dialysis fluid in a uniform flow state and promote the diffusion of small molecule impurities. The entire dialysis process is carried out at a low temperature of 4°C. During the dialysis process, the dialysis fluid is tested regularly. In the early stage, the conductivity of the dialysate can be tested every hour with a portable conductivity meter to determine the leakage of small molecular ions; the dialysate should be replaced in time according to the test results. Within the first 3 hours of dialysis, the dialysate should be replaced every 1-2 hours; as the dialysis continues, the concentration of impurities in the dialysate gradually decreases, and the time interval for replacing the dialysate can be extended to once every 2-3 hours. When the conductivity of the dialysate remains basically unchanged for two consecutive tests, and no obvious impurity ions are detected by ion chromatography and other detection methods, it indicates that the dialysis has reached the end point. Take out the dialysis bag, gently absorb the moisture on the surface of the dialysis bag with filter paper, then open the dialysis bag, and transfer the solution in the bag to a clean container that has been sterilized at high temperature to obtain a relatively pure oxidized bacterial cellulose (OBC) solution.

[0071] (6) Oxidized bacterial cellulose, glycerol and citric acid were mixed in a ratio of 10.0 g: 0.3 g: 0.2 g, homogenized for 15 min, and reacted at 80° C.-100° C. for 4 h.

[0072] (7) Tea polyphenols (TP) were added into the system at 0.1 g / mL and subjected to ultrasonic loading for 30-60 min. Finally, oxidized bacterial cellulose-glycerol-tea polyphenols (OBC-GL-TP) was obtained.

[0073] Test Example 1

[0074] Determination of antibacterial properties of coatings

[0075] In this embodiment, two bacteria, Escherichia coli and Staphylococcus aureus, were used to carry out antibacterial experiments, and the antibacterial properties of OBC-GL, OBC-TP, and OBC-GL-TP were determined through growth curve tests.

[0076] For the growth curve test, 10 mL of the materials obtained in Examples 1 to 3: OBC-GL, OBC-TP and OBC-GL-TP were added to 100 mL of liquid culture medium, and then 1 mL of bacterial culture solution was added and cultured in a shaker at 37°C and 160 rpm. The absorbance at 600 nm was measured every 2 hours, and each test was repeated 3 times.

[0077] Among them, Abs 空白 and Abs 试验 They are the absorbance of the blank group and different sample test groups at 600nm. Figure 2 The left and right figures are the growth curves of Escherichia coli and Staphylococcus aureus, respectively. The blank control group had the fastest growth rate because no sample was added. The growth rate of bacteria was significantly inhibited after adding OBC-TP and OBC-GL, which may be related to the active compounds in tea polyphenols (TP). Because it can penetrate into the cell membrane of microorganisms, destroy its integrity, and cause leakage of intracellular substances. Tea polyphenols (TP) can also affect the metabolic activity of microorganisms by inhibiting enzymes in microorganisms.

[0078] Test Example 2

[0079] Determination of oxidation resistance of coatings

[0080] The oxidation resistance of the coatings was determined by DPPH and ABTS methods.

[0081] (1) For the DPPH test, different coating samples (0.3 μL) were mixed with 1 mL of DPPH ethanol solution (0.1 mmol / L). After dark reaction for 30 min, the absorbance was measured at a wavelength of 517 nm.

[0082] (2) The working solution of the ABTS experiment was 7 mM ABTS stock solution and 2.45 mM potassium persulfate, which was reacted in the dark at room temperature for 12 h. The solution was then diluted with deionized water to obtain an absorbance of 0.70 ± 0.02 at 734 nm. Different coating samples (0.3 μL) were mixed with 1 mL ABTS solution in the dark for 30 min, and the absorbance of the mixture was measured at a wavelength of 734 nm. The free radical scavenging rate (RSA) was calculated as follows:

[0083] RSA(%)=(A 空白 -A 样品 ) / A 空白 ×100

[0084] Among them, A 空白 is the absorbance of the blank group, A 样品 is the absorbance of the test group.

[0085] The results are as follows Figure 3 As shown on the left and right, the antioxidant capacity of all samples is dose-dependent. The antioxidant activity of OBC-GL mainly comes from the carboxyl group at the C6 position in OBC. The scavenging rates of OBC-GL for ABTS and DPPH free radicals are about 35% and 20%, respectively. The scavenging rates of OBC-TP for ABTS and DPPH free radicals are about 40% and 55%, respectively. OBC-GL-TP significantly improved the antioxidant activity of the coating, and the scavenging rates of OBC-GL-TP for DPPH and ABTS free radicals were about 55% and 75%, respectively. This is due to the strong antioxidant activity of TP after loading. TP contains 3 phenolic hydroxyl groups, 1 hydroxyl group, 1 ether bond, and abundant hydroxyl and carboxyl functional groups. At the position of the aromatic ring, there are one or more hydroxyl or methoxy functional groups on the catechin unit. In addition, there are functional groups such as aldehyde groups, which have good free radical scavenging ability.

[0086] Test Example 3

[0087] Application of coating in storage of fresh walnut kernels

[0088] Take OBC-GL-TP and place the walnut in the membrane solution for 2 seconds to completely coat it with the active coating. Depending on the size of the walnut, 1 mL can preserve about 2 walnuts.

[0089] Figures 4 to 6 The changes of acid value (AV), peroxidase (POD) and polyphenol oxidase activity (PPO) in fresh walnut kernels during storage.

[0090] (1) Acid value (AV) can be used as an indicator of the degree of oil deterioration. The hot ethanol method uses the walnut oil extracted during the determination of crude fat, and the determination is made according to GB5009.229-2016, with slight changes. During titration, first take 50 mL of 95% ethanol and add it to a conical flask, then add 0.5 mL of phenolphthalein indicator, put the conical flask in a water bath at 90°C to 100°C and heat until the ethanol is slightly boiling. Take out the conical flask and immediately titrate with 0.01 mol / L potassium hydroxide. The solution changes color and remains unchanged for 15 seconds, which is the titration end point. Then weigh 0.2 g of kernel oil in a conical flask, pour the neutralized ethanol into it, and then put it in a water bath at 90°C to 100°C and heat until the ethanol is slightly boiling. During this period, shake the conical flask vigorously to form a suspension. Finally, take out the conical flask and titrate with potassium hydroxide standard solution while it is hot. Shake the conical flask continuously during titration. The titration endpoint is when the solution changes color and remains for 15 seconds. Record the number of milliliters of alkali solution consumed. Repeat each experiment 3 times. (Approximate reference range: 0.2mg / g-0.8mg / g)

[0091] The acid value (also known as acid number) is calculated according to the following formula:

[0092] X = ((v-v0) × c × 56.1) / m;

[0093] Where:

[0094] X—acid value, in milligrams per gram (mg / g);

[0095] V—The volume of the standard titration solution consumed in the sample determination, in milliliters (mL);

[0096] V0—the volume of the standard titration solution consumed by the corresponding blank determination, in milliliters (mL), V0=0;

[0097] c—the molar concentration of the standard titration solution, in moles per liter (mol / L);

[0098] 56.1—The molar mass of potassium hydroxide in grams per mole (g / mol);

[0099] m—weight of the oil sample, in grams (g).

[0100] If the acid value is ≤1mg / g, the calculation result shall be rounded to 2 decimal places; if the acid value is 1mg / g<≤100mg / g, the calculation result shall be rounded to 1 decimal place; if the acid value is >100mg / g, the calculation result shall be rounded to the integer.

[0101] Precision: When the acid value is <1 mg / g, the absolute difference between two independent determination results obtained under repeated conditions shall not exceed 15% of the arithmetic mean; when the acid value is ≥1 mg / g, the absolute difference between two independent determination results obtained under repeated conditions shall not exceed 12% of the arithmetic mean.

[0102] like Figure 4 As shown in the figure, the AV values ​​of all samples increased with the increase of storage time. During the entire storage period, there was no significant difference in the AV values ​​between OBC-GL, OBC-TP and the control group, while the OBC-GL-TP treatment significantly delayed the increase in AV values, indicating that the OBC-GL-TP coating can effectively delay the deterioration of oil. This is because the TP in OBC-GL-TP is slowly released to the surface of walnuts, providing hydrogen atoms for the lipid free fatty acid content and removing them, thereby interrupting the oxidation process of fatty acids and preventing the increase of acid value.

[0103] (2) Peroxidase (POD) activity is one of the key enzymes in the enzymatic defense system of plants under adverse conditions and is a key indicator for measuring the preservation effect of walnuts. Weigh 1g of kernels, homogenize with 8mL of 0.1mol / L sodium phosphate buffer (pH6.8) (containing 1% (v / v) tritonX-100 and 4 (w / w)% pvp) in an ice bath, and centrifuge at 10000×g at 4℃ for 20min. The supernatant is used for POD and PPO activity determination.

[0104] The POD reaction mixture includes 1 mL of supernatant, 1 mL of sodium phosphate buffer (0.1 mol / L, pH 6.8), and 3 mL of guaiacol solution (25 mmol / L). After adding 0.2 mL of 2% H2O2 solution, the change in absorbance within 5 min was immediately measured at 470 nm. The enzyme activity was calculated as U g-1FW, and a change of 0.01 in absorbance within 1 min was defined as one enzyme unit (U).

[0105] Depend on Figure 5It can be seen that with the increase of storage days, the POD values ​​of all groups showed a trend of first increasing and then decreasing. During the entire storage period, the POD value change trends of the OBC-GL, OBC-TP and vacuum groups were relatively similar, and there was no significant difference between them. The OBC-GL-TP treatment group showed significantly different characteristics throughout the process, which significantly delayed the increase of the POD value. This is mainly attributed to the sustained release effect of TP in OBC-GL-TP. During the storage of walnuts, TP was gradually released to the surface of walnuts. TP itself has antioxidant properties, and it can effectively capture and remove reactive oxygen species produced during cell metabolism, such as superoxide anion free radicals, hydroxyl free radicals, etc. These reactive oxygen species usually induce increased peroxidase activity, and TP reduces the stimulation of peroxidase by removing them, thereby inhibiting the rapid increase of peroxidase activity, which ultimately helps to preserve the freshness of walnuts and maintain good quality during storage.

[0106] (3) Polyphenol oxidase (PPO) can catalyze and accelerate the degradation of phenol, causing browning of fruits and vegetables. Experimental method: Weigh 1g of kernel, add 8mL of 0.1mol / L sodium phosphate buffer (pH 6.8) (containing 1% (v / v) tritonX-100 and 4 (w / w)% pvp) and homogenize in an ice bath, and centrifuge at 10000g for 20min. Take 0.5mL of supernatant, add 2mL of sodium phosphate buffer (0.1mol / L, pH 6.8) and 2mL of catechol solution (50mmol / L) and mix well. After adding 0.2mL of H2O2 solution (2%), immediately measure the change in absorbance at 470nm within 5min. Enzyme activity is calculated as U g -1 FW, a change in absorbance of 0.1 within 1 min was defined as one enzyme activity unit (U).

[0107] like Figure 6 As shown in the figure, compared with the blank group, the vacuum group showed almost no effect of inhibiting PPO activity in the first 36 days, while OBC-GL and OBC-TP treatments significantly inhibited the increase of PPO activity and there was no significant difference between the two groups at multiple time points. OBC-GL-TP further enhanced this effect. This indicates that TP is slowly released onto the surface of walnuts during storage. Tea polyphenols have antioxidant and enzyme inhibitory properties. They can bind to the active sites of polyphenol oxidase or reduce the activation of polyphenol oxidase by removing reactive oxygen species that trigger increased enzyme activity, thereby inhibiting the rapid increase of polyphenol oxidase activity. This inhibitory effect helps to reduce the degradation of phenol in walnuts, thereby reducing the possibility of browning of walnuts, which is beneficial for walnuts to maintain a good appearance and quality during storage and extend their shelf life.

[0108] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.

Claims

1. A method for preparing an oxidized bacterial cellulose-glycerol-tea polyphenols fresh-keeping coating material, characterized in that: The preparation method comprises the following steps: S1. Preparation / obtaining of bacterial cellulose; S2. crushing and oxidizing the bacterial cellulose to obtain oxidized bacterial cellulose; S3. The oxidized bacterial cellulose obtained in step S2 is mixed with glycerol and citric acid to carry out a grafting reaction to obtain oxidized bacterial cellulose-glycerol; S4. The oxidized bacterial cellulose-glycerol obtained in step S3 is mixed with tea polyphenols for reaction, so that the tea polyphenols are loaded on the oxidized bacterial cellulose-glycerol, and the oxidized bacterial cellulose-glycerol-tea polyphenols fresh-keeping coating material is obtained.

2. The method for preparing an oxidized bacterial cellulose-glycerol-tea polyphenols fresh-keeping coating material according to claim 1, characterized in that: In step S1, the source of the bacterial cellulose is selected from any one of the bacteria of the genus Acetobacter, Agrobacterium, Rhizobium or Sarcina.

3. The method for preparing an oxidized bacterial cellulose-glycerol-tea polyphenols fresh-keeping coating material according to claim 1, characterized in that: In step S2, the bacterial cellulose is crushed to prepare a homogenate with a mass concentration of 0.1-2%, oxidized in a TEMPO / NaBr / NaClO mixed oxidation system at room temperature, and then centrifuged, washed and dialyzed to obtain oxidized bacterial cellulose.

4. The method for preparing an oxidized bacterial cellulose-glycerol-tea polyphenols fresh-keeping coating material according to claim 3, characterized in that: The oxidation time is 0.5-5h.

5. The method for preparing an oxidized bacterial cellulose-glycerol-tea polyphenols fresh-keeping coating material according to claim 4, characterized in that: The TEMPO / NaBr / NaClO mixed oxidation system is as follows: the amount of TEMPO is (0.1-1.0) g / 100 mL bacterial cellulose; the amount of NaBr is (0.1-1.0) g / 100 mL bacterial cellulose; the mass concentration of the NaClO solution is 8-12%, and the amount is 8-10 mL.

6. The method for preparing an oxidized bacterial cellulose-glycerol-tea polyphenols fresh-keeping coating material according to claim 5, characterized in that: The mixed oxidation steps are as follows: The bacterial cellulose homogenate with a mass concentration of 0.1-2% is mixed with TEMPO, NaBr and NaClO, and then sodium hydroxide is added to maintain the pH value at 9.9-10.1; when the pH value no longer decreases, 10% ethanol is added to quench the reaction.

7. The method for preparing an oxidized bacterial cellulose-glycerol-tea polyphenols fresh-keeping coating material according to claim 1, characterized in that: In step S3, the ratio of oxidized bacterial cellulose, glycerol and citric acid is (1.0-10.0) g: (0.03-0.3) g: (0.02-0.2) g, the homogenization time is 10-30 min, and the mixing reaction is carried out at 80° C.-100° C. for 4-6 h.

8. The method for preparing an oxidized bacterial cellulose-glycerol-tea polyphenols fresh-keeping coating material according to claim 1, characterized in that: In step S4, the time for the mixed reaction of the oxidized bacterial cellulose-glycerol and tea polyphenols is 30-60 minutes.

9. An oxidized bacterial cellulose-glycerol-tea polyphenols fresh-keeping coating material, characterized in that: It is prepared by the method according to any one of claims 1 to 8.

10. The use of an oxidized bacterial cellulose-glycerol-tea polyphenols fresh-keeping coating material as claimed in claim 9, characterized in that: The oxidized bacterial cellulose-glycerol-tea polyphenols fresh-keeping coating material is used as a fresh-keeping coating for food preservation.

Citation Information

Patent Citations

  • Packaging film for refrigerated foods and preparation method thereof

    CN102212209B

  • Preparation method of bacterial cellulose-tea polyphenol composite antibacterial membrane

    CN106633156A